Potential role in seed dispersal revealed by experimental trials with captive southern muriquis (Brachyteles arachnoides) - Zanette, E. M.; Fuzessy, L. F. [UNESP]; Hack, R. O.E.; Monteiro-Filho, E. L.A. (Springer Nature, 2020)
Primates are great fruit consumers and disperse intact seeds from most of the plants they consume, but effective seed dispersal depends, amongst other factors, on handling behavior. Likewise, the treatment in gut and mouth may alter seed fate. Overall, frugivore and folivore-frugivore primates are recognized to provide beneficial gut treatment for Neotropical plant species, but this effect might be overlooked at species-specific levels. In this study, we assessed the role of the southern muriqui (Brachyteles arachnoides), an endangered and endemic primate living in restricted fragments of the Brazilian Atlantic Forest, on potential quality of seed dispersal of native plants. Our main goals were to understand the effect of seed ingestion by this large-bodied atelid on germination of defecated seeds and in seed recovery by offering wild fruits of native species to captive individuals. We found that seven out of nine plant species were defecated intact and were able to germinate. Of those seven, one species showed enhanced and another showed decreased germination potential after defecation, while three species germinated faster after being defecated. The remaining species showed no differences from control seeds. The two non-germinating species were heavily predated, and average seed recovery was lower than expected, suggesting high levels of seed predation. The largest species offered (Inga vulpina) showed the highest dispersal potential. Our data support an overall neutral or potentially positive role of southern muriquis in seed dispersal quality for seven out of nine Atlantic Forest plant species, highlighting these primates’ potential to produce an effective seed rain.
Keywords: Allochthone disperser; Endozoochory; Primate seed dispersal; Seed germination; Seed predation; Tropical forest